2011
DOI: 10.1007/s11270-011-0761-5
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Microorganisms for Biodegradation of Simazine Pollution (Obsolete Pesticide Azotop 50 WP)

Abstract: The capability of environmental microorganisms to biodegrade simazine—an active substance of 2-chloro-s-triazine herbicides (pesticide waste since 2007)—was assessed. An enormous metabolic potential of microorganisms impels to explore the possibilities of using them as an alternative way for thermal and chemical methods of utilization. First, the biotope rich in microorganisms resistant to simazine was examined. Only the higher dose of simazine (100 mg/l) had an actual influence on quantity of bacteria and env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 34 publications
0
13
0
4
Order By: Relevance
“…Company Fregata S.A. in Gdansk (production division in Waćmierz) had used the biological technology -inactivating washings and pesticide residues by means of biological method in bioreactor with fixed active bed to clean the industrial wastewater. Installing, converting 550 Mg waste annually, is effective, simple and above all safe for the environment (Błaszak et al 2011). Knowing the composition of washings (in the factory -as opposed to the landfill -the variety of chemicals is small), it can be easier to fit the appropriate composition of the vaccine.…”
Section: The Use Of Biological Methods For the Elimination Of Pesticimentioning
confidence: 99%
“…Company Fregata S.A. in Gdansk (production division in Waćmierz) had used the biological technology -inactivating washings and pesticide residues by means of biological method in bioreactor with fixed active bed to clean the industrial wastewater. Installing, converting 550 Mg waste annually, is effective, simple and above all safe for the environment (Błaszak et al 2011). Knowing the composition of washings (in the factory -as opposed to the landfill -the variety of chemicals is small), it can be easier to fit the appropriate composition of the vaccine.…”
Section: The Use Of Biological Methods For the Elimination Of Pesticimentioning
confidence: 99%
“…These processes are appropriate for application in all countries because they are cost-effective and relatively simple to implement. Bioremediation can take place under aerobic and anaerobic conditions [25,111,133,221]. The science of bioremediation is important for both in situ bioremediation and in applications where pesticide-contaminated soil is treated using composting, land farming or biopiles [34,111,264,277,279,283,284].…”
Section: Remediation Of Pesticidesmentioning
confidence: 99%
“…There has been significant progress in developing in situ bioremediation for pesticides [25,[86][87][88]92,111,112,134,151,154,159,162,[180][181][182]185,188,202,204,206,244,277,283,284,286]. These methods fall into three general categories; phytoremediation, bioremediation by indigenous organisms and bioaugmentation.…”
Section: In Situ Bioremediation and Phytoremediationmentioning
confidence: 99%
“…In our study, only the woodlands showed a different pattern in terms of pesticide degradation when comparing sites close and distal to the river. However, we hypothesized that the negative correlation between simazine degradation and N and P inorganic forms content could explain this spatial variability as the use of pesticides as a source of energy in areas with low nutrient status has been identified (Błaszak et al, 2011). In addition, it has been shown that some organisms (e.g.…”
Section: Pollutant Removal Through Degradationmentioning
confidence: 99%
“…In addition, it has been shown that some organisms (e.g. Pseudomonas) are able to mineralise simazine more rapidly (Regitano, 2006;Błaszak et al, 2011) and therefore a more diverse microbial population associated with a higher above-ground plant diversity could be involved in different ecosystems. Our results may therefore reflect the spatial heterogeneity of microbial populations within these habitat types rather than a specialization of microbial population in riparian areas.…”
Section: Pollutant Removal Through Degradationmentioning
confidence: 99%